PENGARUH KERAGAMAN PRODUK, KUALITAS PELAYANAN DAN PENGALAMAN PENGGUNA TERHADAP KEPUTUSAN PEMBELIAN APOTEK K24 DI SENOPATI, SEDATI - Mega Ayuh Rochmah; Arif Rachman Putra (Lembaga Pengembangan Kinerja Dosen, 2025)
This study sought to ascertain and investigate how Apotek K24 Senopati, Sedati, customer happiness, product variants, and service quality affected decisions to buy. Customers of Apotek K24 made up the study's population, and 100 responses made up the sample. Quantitative research methodology was employed. Multiple linear regression and hypothesis testing were the methods of analysis employed.